Synthesis, growth, structure and characterization of potassium lithium hydrogen phthalate mixed crystals1. Issue 57 (25th June 2015) - Manonmoni, J. Vijila; Ramasamy, G.; Prasad, A. Aditya; Meenakshisundaram, S. P.; Amutha, M.
<x xml:space="preserve">Abstract</x> Mixed crystals of lithium-incorporated potassium hydrogen phthalate were grown by the slow evaporation solution growth technique from an aqueous solution containing equimolar quantities of potassium hydrogen phthalate (KHP) and lithium carbonate.